2006
DOI: 10.1364/oe.14.011972
|View full text |Cite
|
Sign up to set email alerts
|

Spectral evolution with incremental nanocoating of long period fiber gratings

Abstract: The incremental deposition of a thin overlay on the cladding of a long-period fiber grating (LPFG) induces important resonance wavelength shifts in the transmission spectrum. The phenomenon is proved theoretically with a vectorial method based on hybrid modes and coupled mode theory, and experimentally with electrostatic self-assembly monolayer process. The phenomenon is repeated periodically for specific overlay thickness values with the particularity that the shape of the resonance wavelength shift depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Recent interest in the one-dimensional PC involving optically linear media has largely focused on numerical studies of the in-gap transmission modes of finite and symmetric systems. It was shown in the case of a singlelayer defect, [4][5][6] the position of a photonic pass-band (PPB) in the photonic band-gap (PBG) could be varied by changing the refractive index of the defect layer without affecting its peak transmittance. In a study for exploring new functionalities, it was demonstrated numerically, 7) that basically the same feature was found in the case of asymmetric PC with two identical defect layers, with more sensitive effect of the defect thickness on the width of the PPB.…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in the one-dimensional PC involving optically linear media has largely focused on numerical studies of the in-gap transmission modes of finite and symmetric systems. It was shown in the case of a singlelayer defect, [4][5][6] the position of a photonic pass-band (PPB) in the photonic band-gap (PBG) could be varied by changing the refractive index of the defect layer without affecting its peak transmittance. In a study for exploring new functionalities, it was demonstrated numerically, 7) that basically the same feature was found in the case of asymmetric PC with two identical defect layers, with more sensitive effect of the defect thickness on the width of the PPB.…”
Section: Introductionmentioning
confidence: 99%
“…An LPG operating in this was demonstrated in [26]. While there are a number of theoretical treatments of coated LPGs [47], a significant limitation in their use for predicating the optimal parameters lies in the accuracy with which the optical fibre and coating material parameters are known, which can create significant discrepancies in the predictions of the model, particularly for coupling to higher order modes at the PMTP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, changing the HRI could also result in cladding modes reorganization. The theoretical and experimental study proposed by Del Villar et al showed that by selecting an appropriate overlay thickness, the highest sensitivity of the resonance wavelengths to HRI change of the overlay can be obtained [10,11].…”
Section: Long Period Gratings (Lpg)mentioning
confidence: 99%